PENDIDIKAN KARAKTER PERSPEKTIF HADITS PADA MATA PELAJARAN MATEMATIKA DI SEKOLAH DASAR - Hilmi, Nasywa; Br Sinuhaji, Fara Ulfa; Lessy, Zulkipli (IAIN Pontianak, 2024)
Moral degradation that currently occurs in students, especially at the elementary school level. Character education in the realm of education in the level of elementary school is very important to instill because basic education is the beginning of the application of morals in human life. Character education from the hadith perspective in mathematics subjects in elementary schools is believed to contribute in the academic realm in character improvement. The purpose of this study is to examine character education in the perspective of hadith in elementary school. Method used in this study is library research where the primary source of information and data is documents, such as relevant journals and books. Based on the literature review collected, it was found that the absolute source of knowledge is the Qur’an and hadith. In both sources, there is no dichotomy of knowledge. The results showed that character education from the hadith perspective in mathematics subjects in elementary schools using LKPD was valid, practical, and effective.